Exploring how members of the public access and use health research and information: a scoping review - Celayne Heaton-Shrestha; Kristin Hanson; Sophia Quirke-McFarlane; Nancy Delaney; Tushna Vandrevala; Lindsay Bearne (BMC, 2023)
Abstract Background Making high-quality health and care information available to members of the general public is crucial to support populations with self-care and improve health outcomes. While attention has been paid to how the public accesses and uses health information generally (including personal records, commercial product information or reviews on healthcare practitioners and organisations) and how practitioners and policy-makers access health research evidence, no overview exists of the way that the public accesses and uses high quality health and care information. Purpose This scoping review aimed to map research evidence on how the public accesses and uses a specific type of health information, namely health research and information that does not include personal, product and organisational information. Methods Electronic database searches [CINAHL Plus, MEDLINE, PsycInfo, Social Sciences Full Text, Web of Science and SCOPUS] for English language studies of any research design published between 2010-2022 on the public's access and use of health research or information (as defined above). Data extraction and analysis was informed by the Joanna Briggs Institute protocol for scoping reviews, and reported in accordance with the PRISMA extension for scoping reviews. Results The search identified 4410 records. Following screening of 234 full text studies, 130 studies were included. One-hundred-and-twenty-nine studies reported on the public's sources of health-research or information; 56 reported the reasons for accessing health research or information and 14 reported on the use of this research and information. The scoping exercise identified a substantial literature on the broader concept of 'health information' but a lack of reporting of the general public's access to and use of health research. It found that 'traditional' sources of information are still relevant alongside newer sources; knowledge of barriers to accessing information focused on personal barriers and on independent searching, while less attention had been paid to barriers to access through other people and settings, people's lived experiences, and the cultural knowledge required. Conclusions The review identified areas where future primary and secondary research would enhance current understanding of how the public accesses and utilises health research or information, and contribute to emerging areas of research.